PENGEMBANGAN MATERI AJAR MENULIS TEKS DESKRIPSI BERBASIS WISATA RELIGI KOTA MAKASSAR - Alam, Anisa Maulidiah; Usman, Usman; Sultan, Sultan (Manifestasi: Jurnal Pendidikan dan Pengajaran, 2021)
This research aims: (1) knowing the form of teaching material writing a description text based on religious tourism makassar city in Class VII junior high school; (2) test the feasibility of teaching material writing a description text based on religious tourism of Makassar City in Class VII junior high school. This research is research and development that uses Borg and Gall theory by adapting Sugiyono's development steps, namely preliminary study of potential and problems, product design, and validation tests. This research resulted in a product of teaching material writing the description text and obtained the final results of validator assessment of the teaching material showed that the content feasibility component of the average of 0.89 categories was very feasible, the presentation feasibility component obtained an average of 0.91 categories very feasible, the language component obtained an average of 0.94 categories very feasible, graph components obtained an average of 0.91 categories very decent, and the implication component to the development of text writing. The description earns an average of 0.92 very decent categories.